From Mongolia to Khwārazm: The Qonggirad Migrations in the Jochid Ulus (13th.-15th. c.) - Ishayahu Landa (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: The article discusses the Qonggirad migration to the Jochid ulus in the aftermath of the Mongol conquests as well as the roles the Qonggirad elite played in the Jochid and Khwārazmian political history in the late 13th – early 15th centuries. Based on genealogical and numismatic analyses, this paper, on the one hand, provides insights into the formation and developments of the autonomous Qonggirad power in Khwārazm in the second half of the 14th century and, on the other hand, stresses the importance of the Islamisation for the Mongol tribal elite’s accustomisation to the regional and geopolitical historical setting during the troubled period of 1359-1380s in the Jochid ulus.